Nivel de conocimiento y uso de métodos anticonceptivos en adolescentes de la Unidad Educativa Fiscal “Tcrn. Lauro Guerrero” - Salinas Ríos, Paula Geraldine (2023)
A large part of the students of the various educational institutes of Ecuador begin to experience their sexual life without taking into account the consequences that such acts may have such as sexually transmitted diseases or premature pregnancy product of misinformation about contraceptive methods. The current research focuses on the impact of the problem by determining the level of knowledge and use of contraceptive methods in adolescents of the Unidad Educativa Fiscal "Tcrn. Lauro Guerrero", in addition to identifying the most used and known contraceptive method, a matrix was also made in conjunction with an educational triptych to disseminate health promotion actions and improve knowledge of the subject. A descriptive, observational and prospective cross-sectional cohort study was carried out using previously elaborated surveys. A total of 129 students participated out of 203 students from the second to third year of high school at the institution, using a non-probabilistic sample. It was found that most of the students have an average knowledge about contraceptive methods; while a minimum percentage has a low knowledge; demonstrating that the condom is the most used and known contraceptive method. A matrix was proposed to improve the knowledge of young people, which is available to the institution. In conclusion, the sample under study has a lack of knowledge about the importance of the life project and the aforementioned rights, which leads to limited information about contraceptive methods, leading them to make many mistakes that can harm their health and their lives.